GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) COVID-19 DI KOTA SOLOK - Adhima Indriyani; Eryati Darwin; Syandrez Prima Putra; Nita Afriani; Firdawati Firdawati (SINERGI : Jurnal Riset Ilmiah, 2026)
Covid-19 is an infectious disease caused by SARS-CoV-2 virus. Many people are worried about getting vaccinated because they received false rumors about KIPI Covid-19 which can cause death by using several types of vaccines. Objective: This study aims to describe the level of public knowledge about Covid-19 Post-Immunization Follow-up Events (KIPI) in Solok City. Methode: This research is a quantitative descriptive study, which is to see a variable description of the level of public knowledge regarding KIPI Covid-19 based on the characteristics of respondents. Sampling using simple random sampling method on 100 respondents. Result: In this study, the results were obtained: only 36% of respondents had received the third dose of Covid-19 vaccination, 52% of respondents had insufficient knowledge regarding KIPI Covid-19, and 57% of respondents experienced Covid-19 Post Immunization Follow-Up Events (KIPI). There is no association between gender, age, education level, and employment status with knowledge of Covid-19 Post Immunization Follow-Up Events (KIPI). There is a significant association between vaccination status with knowledge of Covid-19 Post Immunization Follow-Up Events (KIPI). Conclusion: There were more respondents who have less knowledge (more than half of the respondents). When viewed from the vaccination status, more respondents with less knowledge got vaccinated up to the second dose.